A Psychoeducational Perspective of Discipline in Schools and the Abolishing of Corporal Punishment*. (1st August 2016) - Shaikhnag, Noorullah; Assan, Thomas Edwin Buabeng; Loate, Irene Madiala
Abstract: Media reports suggest that students in many schools, especially rural schools, display arrogance, violence, rudeness, truancy and other types of misconduct. In the light of above and with the implications of the implementation of the Schools Act in mind, it was investigated whether the South African government's decision to abolish physical punishment was viable and whether it had any impact on student conduct. A sample was drawn of 400 learners and 100 teachers from 10 high schools in an educational region of the North West Province of South Africa. The main objective of the study was to investigate the effects of the abolition of physical punishment on discipline. In contrast to the thrust of the theoretical investigation that revealed that the abolition of corporal punishment would probably lead to an increase in poor behavior, the empirical investigation, particularly the application of the Chi-square test, indicated no positive relationship between the abolition of corporal punishment and increase in misconduct. The study recommends that alternative forms of disciplinary measures are necessary to replace corporal punishment in order to improve the teaching/learning situation.